Implementasi Aplikasi Penjualan dan Laporan Pendapatan Restoran King Royal Hotel Berbasis Mobile - Primanando Alfian Dwinatha; Vidi Sandi (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2026)
King Royal Hotel Restaurant still applies manual sales transaction recording, causing data management and revenue report preparation to be less than optimal. This study aims to design and implement a Flutter-based sales and revenue reporting application that utilizes local storage as a data storage mechanism on the device. The system development method used is the Waterfall method, which includes the stages of requirements analysis, design, implementation, testing, and maintenance. The application was developed using the Flutter framework with the Dart programming language and utilizes the shared_preferences and hive packages for local data management on the device without requiring an internet connection or external database server. In addition, the application is designed to be easy for restaurant employees to use in recording daily transactions more quickly and accurately. Testing was conducted using the Black Box Testing method, which showed that all application features functioned according to functional requirements. The results of the study indicate that the Flutter-based application with a local storage approach is capable of improving transaction recording efficiency and generating revenue reports automatically at King Royal Hotel Restaurant.